2014
DOI: 10.4306/pi.2014.11.4.476
|View full text |Cite
|
Sign up to set email alerts
|

Association of SNAP-25 GeneDdel andMnll Polymorphisms with Adult Attention Deficit Hyperactivity Disorder

Abstract: ObjectiveThe synaptosomal-associated protein of 25 kDa (SNAP-25) gene is a presynaptic plasma membrane protein and an integral component of the vesicle docking and fusion machinery mediating secretion of neurotransmitters. Previously, several studies reported association between SNAP-25 and attention deficit hyperactivity disorder (ADHD). We investigated whether these SNAP-25 polymorphisms (MnlI T/G and DdelI T/C) were also associated with ADHD in the Turkish population.MethodsOur study comprised unrelated 139… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The high prevalence of Attention deficit hyperactivity disorder necessitates the understanding of the etiology, as well as the development of approaches for diagnosis and treatment of this disorder. 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high prevalence of Attention deficit hyperactivity disorder necessitates the understanding of the etiology, as well as the development of approaches for diagnosis and treatment of this disorder. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Significant associations have been shown between DAT-1 , DRD4 , DRD5 , 5HTT , HTR1B and SNAP-25 genes and the ADHD. 5 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…Most recently, a study by Herken et al with 139 cases and 73 controls in a Turkish population found that there was a statistically increased ADHD risk in persons carrying G allele ( p<0.001) but not with SNAP-25 DdeI(rs1051312) (Herken et al, 2014). Our meta-analysis showed that a strong M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 9 association existed between the rs3746544 polymorphism and ADHD in the studies using an Asian population, but not in studies with Caucasian participants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, four family-based studies have shown that these two SNPs are associated with increased risk of ADHD (Barr et al, 2000;Brophy et al, 2002;Kustanovich et al, 2003;Mill et al, 2004). However, the findings from subsequent case-control studies have been inconsistent, and this discrepancy may be due to inadequate statistical power, ethnic differences and publication bias (Barr et al, 2000;Pazvantoglu et al, 2013;Sarkar et al, 2012;Galvez et al, 2014;Choi et al, 2007;Zhao AL et al, 2007;Herken et al, 2014).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Another important role of synapsin III is involved in synaptic transmission, especially dopamine release [10]. Studies have investigated genes encoding the proteins that have roles in the modulation of neurotransmitter release and ADHD, such as SNAP-25 gene (the synaptosomal-associated protein) [11], synaptobrevin-2 (VAMP2) and syntaxin 1A genes [12]. This inquiry about synapsin III in ADHD is commendable as ADHD is related to the release of neurotransmitters, especially dopamine.…”
Section: Introductionmentioning
confidence: 99%